Современный инженер: место языковой подготовки в системе профессионального образования - Воробьёва Л. В. Людмила Владимировна; Курикова Н. В. Наталья Владимировна; Максимов В. В. Владимир Владимирович; Никанорова Ю. В. Юлия Владимировна; Тюрина И. И. Ирина Ивановна (2022, 2022)
Заглавие с экрана